Discrimination in Zootopia: A critical reading - Hianly Muljadi (EduLite: Journal of English Education, Literature and Culture, 2019)
This research is an analysis of an animation movie by Walt Disney Animation Studios entitled Zootopia. The story of Zootopia, just like other animation movies which can be generalized as intended for children. It contains a positive message which can be seen from the tagline of this movie; “This is Zootopia. Anyone can be Anything”. However, this research tries ascertaining the opposite as it can be seen that the message of the movie is not entirely true. It is under descriptively qualitative method supported by the Theory of Deconstruction as a framework -- that a text can betray itself and this movie is no exception. In Zootopia, just like in human world, the animals are divided into species and kinds or types. This division can clearly lead to discrimination, stereotypes and prejudice. At the end, the notion that anyone can be anything is right to some extend but there are certainly limitations and boundaries that one cannot across to avoid instability in the life of the animals. Thus, the movie can be ‘read’ as having an entirely different message. This research shows that an animation movie can also be interpreted in many ways and may indeed reflect what happens in our reality.